Narracja czasem. Analiza struktury narracyjnej filmu Arrival (2016) Denisa Villeneuve’a - Majer, Artur (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article deals with the narrative structure of Denis Villeneuve’s Arrival. Using the concept of a skeptical viewer as a starting point, the author follows the processes of unveiling meanings, both when it comes to the understanding of the plot of the story, as well as the senses and morals stemming out of it. The viewer’s activity appears to be engaged with the activity of a character who is determined to discover the generic science fiction mystery, i.e. to learn the secret of the aliens’ language. The language, in turn, leads to revealing the time reliances in the film, as well as to formulating the thesis on a specific kind of storytelling: not as a “narrative about time,” but rather a “narrative by time.”